El realisme i la poesia a Mallorca: els poetes de «La Sínia» - Rosselló Bover, Pere (Caplletra. Revista Internacional de Filologia, 2000)
Resum: After a brief discussion of precedents of the realistic movement in Majorcan poetry of the postwar period, this article centres on the collection of “La Sínia”, the principal representative of this trend in Majorca, and in the poets of the 1960s who published their works there (Guillem Frontera, Jaume Pomar, Josep Melià, and Francesc Barceló). Paraules clau: realisme; poesia mallorquina; «La Sínia»; Guillem Frontera; Jaume Pomar; Josep Melià; Francesc Barceló